At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
Step-by-step explanation:
x
(f/g)(x) = -----------
x + 1
Notice that x cannot be -1, which would lead to division by zero. Thus, x = -1 is the vertical asymptote. Also notice that if x grows increasingly large, the fraction shown tends towards x/x, or 1, so we know that the horizontal asymptote is y = 1.
Draw a set of x-y axes and graph y = 1 and x = -1. Plot (0, 0). Again, note that the graph of this function never touches/crosses x = -1. So, for (-1, 0) the graph is a curve caught between x = -1 and x = 0 that increases as x increases. For (0, infinity), the graph heads upward at a slow pace and then levels off nearly parallel to y = 1 (the horizontal asymptote).
As x increases from left to right, y starts out slightly greater than y = 1 and then (while still in Quadrant II) curves upward and approaches the vertical asymptote x = -1.
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.